UNDERSTANDING SELF-GIFT CONSUMER BEHAVIOUR IN INDIA - Arora, Gautam (2007)
Self-gift is a particularly complex class of self-directed consumption or self-indulgence that is hedonistic, special, symbolic, justified and context bound. A self-gift is what it represents to the individual and can be any product, service or experience. It challenges the very fundamental notion of gift giving as a dyadic enterprise and involves a plethora of varied emotions. Research from various studies has suggested that self-gift behaviour may be fairly common in Western society. This empirical investigation rooted in qualitative interpretive principles, has contributed to the consumer behaviour literature by exploring the occurrence of this phenomenon in the Indian context; using 10 semi-structured in-depth online interviews. It provided some initial indicators on how self-gifts may fit into the collectivist Indian culture and also explores the role of gender on self-giving. Its significance lies in the increasing consumerism in India which provides compound opportunities for varied businesses, and has important implications for consumers. Additional exploratory and descriptive research is necessary in order to test and extend these findings. Both the importance of the problem areas and the existence of theoretical bases, demand that the acts and processes of self-gift selection, contexts and the impact of culture and demographics, receive increased attention in future research.